Incorporating Latent Variables into Discrete Choice Models - A Simultaneous Estimation Approach Using SEM Software - Dirk Temme; Marcel Paulssen; Till Dannewald (BuR - Business Research, 2008)
Integrated choice and latent variable (ICLV) models represent a promising new class of models which merge classic choice models with the structural equation approach (SEM) for latent variables. Despite their conceptual appeal, applications of ICLV models in marketing remain rare. We extend previous ICLV applications by first estimating a multinomial choice model and, second, by estimating hierarchical relations between latent variables. An empirical study on travel mode choice clearly demonstrates the value of ICLV models to enhance the understanding of choice processes. In addition to the usually studied directly observable variables such as travel time, we show how abstract motivations such as power and hedonism as well as attitudes such as a desire for flexibility impact on travel mode choice. Furthermore, we show that it is possible to estimate such a complex ICLV model with the widely available structural equation modeling package Mplus. This finding is likely to encourage more widespread application of this appealing model class in the marketing field.
urn:nbn:de:0009-20-16598
Keywords: 650; hybrid choice models; marketing; mode choice; mplus; value-attitude hierarchy; Diskrete Entscheidung; Strukturgleichungsmodell; Marketingtheorie; Operations Research